Estratégia de conversor para interligação de sistemas de geração eólica à rede elétrica - Arrais Junior, Ernano (2014)
Currently, there are several power converter topologies applied to wind power generation. The converters allow the use of wind turbines operating at variable speed, enabling better use of wind forces. The high performance of the converters is being increasingly demanded, mainly because of the increase in the power generation capacity by wind turbines, which gave rise to various converter topologies, such as parallel or multilevel converters. The use of converters allow effective control of the power injected into the grid, either partially, for the case using partial converter, or total control for the case of using full converter. The back-to-back converter is one of the most used topologies in the market today, due to its simple structure, with few components, contributing to robust and reliable performance. In this work, is presented the implementation of a wind cogeneration system using a permanent magnet synchronous generator (PMSG) associated with a back-to-back power converter is proposed, in order to inject active power in an electric power system. The control strategy of the active power delivered to the grid by cogeneration is based on the philosophy of indirect control